Dokumentacja cen transferowych a strategie przedsiębiorstw - Sulik, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Transfer pricing documentation gives tax authorities their first impression of a company and its transfer pricing policy. Such documentation must therefore be prepared with extreme care and consideration, because transfer pricing is usually connected with tax-avoidance strategies. The factual, economic and empirical presentation must be company-, product-, and market-specific, and ail specific internal and external events that impact the company, Financial performance and transfer pricing must be detailed. In preparing documentation, companies are first faced with certain significant strategic decisions. They must determine whether separate documentation must be developed for certain regions or local countries or whether one global analysis will suffice for all of these regions or localities. The companies must also decide how much documentation and information should be provided to the tax authorities to meet these various documentation requirements and avoid any proposed tax adjustments and penalties. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 415-421